Evaluasi Efektivitas Tenaga Kependidikan dalam Meningkatkan Kinerja Guru di SMPN 34 Surabaya - Rahmawati, Diah; Lifdia Kusuma Ningrum, Refkli; Windasari, Windasari; Hanivia Cindy, Agustin (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2024)
This research aims to increase the effectiveness of educational staff in improving teacher performance at SMPN 34 Surabaya. A qualitative approach using case study methodology is the research methodology used. In-depth interviews with teachers and educational professionals, direct observations in schools, and analysis of documents related to teacher professional development programs are the methods used to collect data.The findings of this study show the important role of education personnel in increasing teacher effectiveness at SMPN 34 Surabaya. Educational staff provides training sessions and seminars, assists instructors in their professional growth, and offers adequate administrative assistance. In addition, the availability of competent human resources and efficient staff-teacher communication both support improved teacher performance. However, this research also shows a number of difficulties faced by educational staff when implementing it. These difficulties include heavy workloads, little funding for professional development, and a lack of collaboration within school units.